Revision of Eupines King of New Zealand (Coleoptera: Staphylinidae: Pselaphinae: Goniaceritae) - Shen, Jia-Wei; Leschen, Richard A. B. (Zootaxa, 2020)
The species-rich genus Eupines King of New Zealand is revised to include 48 species, with 22 known species redescribed. Twenty-two new species are described: Eupines (Byraxis) brevis sp. n., E. (B.) caesta sp. n., E. (B.) carinata sp. n., E. (B.) coalita sp. n., E. (B.) complector sp. n., E. (B.) dugdalei sp. n., E. (B.) gigas sp. n., E. (B.) graceae sp. n., E. (B.) huizhenae sp. n., E. (B.) hoarei sp. n., E. (B.) insolita sp. n., E. (B.) mayae sp. n., E. (B.) minuta sp. n., E. (B.) obtusa sp. n., E. (B.) ovalis sp. n., E. (B.) pannicula sp. n., E. (B.) petila sp. n., E. (B.) protibialis sp. n., E. (B.) whirinaki sp. n., E. (B.) waikaremoana sp. n., Eupines (Eupines) undecim sp. n. and Eupines novem sp. n. The following 11 synonymies are proposed: E. (B.) dispar (Sharp) (= E. (B.) munroi Broun syn. n.), E. (B.) hectori Broun (= E. (B.) diversides Newton syn. n.), E. (B.) impar (Sharp) (= E. (B.) sanguineua Broun syn. n., E. (B.) foveatissima Broun syn. n.), E. (B.) monstrosa (Reitter) (= E. (B.) rudicornis Broun syn. n., E. (B.) costata Broun syn. n.), E. (B.) mundula (Schaufuss) (= E. (B.) forficulida Broun syn. n.), E. (B.) paganus (Broun) (= E. (B.) allocera Broun syn. n., E. (B.) sylvicola Broun syn. n., E. (B.) rhyssarthra Broun syn. n.) and Eupinolus altulus (Broun) (= E. (E.) nasuta Broun syn. n.). New combinations are proposed for four species previously described in Eupines: Eupinolus calcaratus (Broun) new comb., Eupinolus nasutus (Broun) new comb., Gastrobothrus ignotus (Broun) new comb. and Gastrobothrus platynotus (Broun) new comb. A key and distribution maps for all New Zealand members of Eupines are provided.